Revealing Students Attitudes (Views and Assessments) on Drug Use in Vocational High Schools in Padang - Rahmi Izzati; Firman Firman; Yanuar Kiram (Universitas Negeri Padang, 2020)
Drug abuse one of the problems that have swept the world and become a frightening problem for the society and Indonesian. Students become one of the targets of drug abuse. Drug abuse occurs during adolescence because adolescents have rapid biological, psychological, and social changes that cause vulnerable individuals to get involved in drug abuse. The cause of drug abuse among adolescents was due to the low attitude of students in addressing the occurrence of drug abuse. The population of this research was the students of SMK in Padang. There were 124 students as the sample of this research. The sampling technique used was a purposive random sampling and the data collection tools used student` attitude instruments used students' attitude instruments in drug abuse with a Likert scale model, with Alpha Cronbach reliability of r=0,991. The data were analyzed by using the descriptive statistical methods with the data processing using SPSS version 22. The results revealed that the students’ attitudes in drug abuse were in the middle category (54.2%). Clearly, the affective component was in the middle category (2.69%); the behavioral component was in the middle category (2.91%); the cognitive component was in the low category (2.47%).